(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Antenatal care (ANC) is the care of a pregnant woman required to ensure a healthy pregnancy and safe childbirth. According to the World Health Organization to achieve the full life-saving potential for pregnant women and babies, minimum four ANC visits are essential. Quality and quantity of ANC visit depends on socio-demographic characteristics, knowledge, awareness and attitude of the individual. To get the benefits from ANC services awareness among pregnant women and their family members are very important. Objective: To evaluate the awareness about ANC service among the pregnant women attending Upazila Health Complex of a rural community. Materials and Methods: This descriptive cross-sectional study was conducted among the pregnant women attending the outpatient department of Kaligonj Upazila Health Complex, Gazipur, Bangladesh from January to March 2017. Data were collected by face-to-face interview of the respondents using a structured questionnaire. Chi-square (χ2) test was done to see the association among the respondents’ socio-demographic characteristics with awareness about ANC services. Result: Respondents’ age range was 16-40 years and 61.9% were below 25 years and 71.1% married before 20 years. More than half (66.5%) of the respondents’ found aware about pregnancy danger sign, safe delivery and benefits of ANC service. This study found a significant (p<0.05) association between socio-demographic characteristics and awareness about ANC services of respondents. Conclusion: Overall knowledge and awareness level on different component and benefits of ANC visit were below the national standard. To improve the community awareness and practice on ANC services community campaign is recommended. Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 11-14